Blood–brain barrier (BBB)-on-a-chip: a promising breakthrough in brain disease research. Issue 19 (25th August 2022) - Peng, Bo; Hao, Shiping; Tong, Ziqiu; Bai, Hua; Pan, Sijun; Lim, Kah-Leong; Li, Lin; Voelcker, Nicolas H.; Huang, Wei
Abstract : This review summarizes recent advances of the integration between BBB-on-a-chip (μBBB) technology and brain disease modeling. It provides a guideline to extend their applications in pathological research, drug development, and personalized medicine. Abstract : The blood–brain barrier (BBB) represents a key challenge in developing brain-penetrating therapeutic molecules. BBB dysfunction is also associated with the onset and progression of various brain diseases. The BBB-on-a-chip (μBBB), an organ-on-chip technology, has emerged as a powerful in vitro platform that closely mimics the human BBB microenvironments. While the μBBB technology has seen wide application in the study of brain cancer, its utility in other brain disease models ("μBBB+") is less appreciated. Based on the advances of the μBBB technology and the evolution of in vitro models for brain diseases over the last decade, we propose the concept of a "μBBB+" system and summarize its major promising applications in pathological studies, personalized medical research, drug development, and multi-organ-on-chip approaches. We believe that such a sophisticated "μBBB+" system is a highly tunable and promising in vitro platform for further advancement of the understanding of brain diseases.